2022
DOI: 10.1101/2022.06.06.494369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitin-based pathway acts inside chloroplasts to regulate photosynthesis

Abstract: Photosynthesis is the energetic basis for most life on Earth, and in plants it operates inside double-membrane-bound organelles called chloroplasts. The photosynthetic apparatus comprises numerous proteins encoded by the nuclear and organellar genomes. Maintenance of this apparatus requires the action of internal chloroplast proteases, but a role for the nucleocytosolic ubiquitin-proteasome system (UPS) was not expected owing to the barrier presented by the double-membrane envelope. Here, we show that photosyn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Nonetheless, there is no clear evidence that these two E3 ligases are directly related to chlorophagy. Very recently, it has been shown by two independent laboratories that much broader chloroplast proteins, even including those resident in internal compartments of the chloroplast, can be targeted for ubiquitination ( Li et al., 2022 ; Sun et al., 2022 ; Trosch, 2022 ). It is therefore intriguing to investigate whether ubiquitin-modified chloroplast proteins can also be a signal to induce chlorophagy.…”
Section: Ubiquitin-dependent Regulation Of Chloroplast Proteinsmentioning
confidence: 99%
“…Nonetheless, there is no clear evidence that these two E3 ligases are directly related to chlorophagy. Very recently, it has been shown by two independent laboratories that much broader chloroplast proteins, even including those resident in internal compartments of the chloroplast, can be targeted for ubiquitination ( Li et al., 2022 ; Sun et al., 2022 ; Trosch, 2022 ). It is therefore intriguing to investigate whether ubiquitin-modified chloroplast proteins can also be a signal to induce chlorophagy.…”
Section: Ubiquitin-dependent Regulation Of Chloroplast Proteinsmentioning
confidence: 99%
“…Among these ubiquitinated proteins were the Rubisco large subunit (RbcL) and ATP synthase subunit beta (AtpB), both of which are chloroplast encoded and degraded through the CHLORAD pathway [ 39 ]. Most recently, an unpublished study by Sun et al demonstrated additional targets of the CHLORAD pathway involved in photosynthesis (i.e., electron transport, energy transduction, and carbon fixation), gene expression, and fatty acid/lipid metabolism [ 126 ]. One important target substrate of interest is fatty acid export 1 (FAX1), an inner chloroplast envelope protein and key player in fatty acid (FA) export.…”
Section: Intra-chloroplast Protein Degradation the Role Of Cdc48mentioning
confidence: 99%
“…One important target substrate of interest is fatty acid export 1 (FAX1), an inner chloroplast envelope protein and key player in fatty acid (FA) export. In the presence of defective CHLORAD-mediated degradation of FAX1, disturbances in cellular metabolic homeostasis (i.e., a notable decrease in cellular lipid species and chloroplast-produced FAs) were observed [ 126 ]. Altogether, these findings raise questions about how intra-chloroplast proteins are selected by the CHLORAD pathway and if intra-chloroplast proteins are marked by ubiquitin inside the organelle [ 39 , 127 ].…”
Section: Intra-chloroplast Protein Degradation the Role Of Cdc48mentioning
confidence: 99%
“…Beyond chloroplast protein import machinery, extensive ubiquitination was recently found in chloroplast fractions, and in greater abundance under UPS or retrotranslocation inhibition. Among these ubiquitinated proteins were the Rubisco large subunit (RbcL) and ATP synthase subunit beta (AtpB), both of which are chloroplast encoded and degraded through the CHLORAD pathway [38] a notable decrease in cellular lipid species and chloroplast-produced FAs) were observed [125]. Altogether, these findings raise questions about how intra-chloroplast proteins are selected by the CHLORAD pathway and if intrachloroplast proteins are marked by ubiquitin inside the organelle [38,126].…”
Section: Role Of Cdc48 In Intra-chloroplast Protein Degradationmentioning
confidence: 99%
“…and carbon fixation), gene expression, and fatty acid/lipid metabolism[125]. One important target substrate of interest is fatty acid export 1 (FAX1), an inner chloroplast envelope protein and key player in fatty acid (FA) export.…”
mentioning
confidence: 99%